2016
DOI: 10.1186/s12880-016-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping breast tissue types by miniature radio-frequency near-field spectroscopy sensor in ex-vivo freshly excised specimens

Abstract: BackgroundReceiving real-time information on tissue properties while performing biopsy procedures has the potential of improving biopsy accuracy. The study goal was to test the ability of a miniature flexible Radio-Frequency (RF) sensor (Dune Medical Devices), designed to be mounted on the surface of surgical tools, in measuring and mapping the various breast tissue types and abnormalities in terms of electrical properties.MethodsBetween January and October 2012, 102 patients undergoing lumpectomy, open-biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…showed that contrast in microwave frequency dielectric properties between malignant and normal adipose‐dominated tissues in the breast is considerable, as large as 10:1, but no benign breast lesions were compared . Previous studies have shown differences in the electrical properties of malignant and benign breast epithelial cells, and that both permittivity and conductivity of breast cancer are significantly higher than those of normal tissues . The values of these properties correlate with frequency, and provide a basis for investigating the mechanisms that underlie malignancy, including cellular proliferation, cytoskeleton, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…showed that contrast in microwave frequency dielectric properties between malignant and normal adipose‐dominated tissues in the breast is considerable, as large as 10:1, but no benign breast lesions were compared . Previous studies have shown differences in the electrical properties of malignant and benign breast epithelial cells, and that both permittivity and conductivity of breast cancer are significantly higher than those of normal tissues . The values of these properties correlate with frequency, and provide a basis for investigating the mechanisms that underlie malignancy, including cellular proliferation, cytoskeleton, and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our results compare favorably to existing margin assessment methods. RF spectroscopy, which has been shown to reduce the re-excision rate in breast-conserving surgery in two studies [16,17], has shown comparable performance in detection of benign breast tissue and carcinoma with a sensitivity and specificity of 90% and 91%, respectively [30]. RF spectroscopy can cover an area large enough to be practical but can currently only be performed ex vivo, leading to challenges of accurate orientation of the resected tumor.…”
Section: Discussionmentioning
confidence: 99%
“…For these applications, there is usually a significant endogenous contrast that can be exploited for imaging. For breast cancer imaging, there is a substantial property contrast between benign and malignant tissue [ 8 , 9 , 10 ]; for stroke diagnosis, there is a large contrast between blood and normal brain tissue [ 11 ]; for bone, there is a significant correlation between the dielectric properties and bone density [ 7 ]. In addition, the dielectric properties can be exploited to recover functional information such as temperature monitoring during thermal therapy [ 12 , 13 ] due to their temperature dependence [ 14 ].…”
Section: Introductionmentioning
confidence: 99%